IMAGE GENERATION METHODS BASED ON NEURAL NETWORKS IN DIGITAL ART AND GRAPHIC DESIGN - Yalg’osheva , Ozoda; Ismailov , Kamoliddin (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article highlights the significance and practical application of image generation methods based on neural networks in digital art and graphic design. With the advancement of artificial intelligence technologies, the image creation process has evolved significantly. Neural networks have enabled the rapid creation of complex graphic compositions, the fusion of diverse artistic styles, and the generation of entirely new visual forms. The article analyzes the operational principles of these technologies, their impact on the design process, and their future development prospects.